2019
DOI: 10.1075/jlp.18065.way
|View full text |Cite
|
Sign up to set email alerts
|

Discourse, music and political communication

Abstract: Political communication is expressed in politicians’ speeches, campaign advertisements and government statements. Politics are also articulated in music, in both traditional political contexts such as anthems and party political broadcasts as well as less traditional contexts including songs, promotional videos and live performances. There is a wide spectrum of opinions as to exactly what are relations between music and politics, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Metaphor does not introduce anything new into the context but actualizes the background knowledge and subconscious representations of the audience, since the interpretation of the metaphor is a purely personal process expressed by the politician; what was said becomes the listener's inner voice and so metaphors can be called the carriers of affective values (Tameryan et al, 2018;Solmaz, 2014;Way 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Metaphor does not introduce anything new into the context but actualizes the background knowledge and subconscious representations of the audience, since the interpretation of the metaphor is a purely personal process expressed by the politician; what was said becomes the listener's inner voice and so metaphors can be called the carriers of affective values (Tameryan et al, 2018;Solmaz, 2014;Way 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Politics is represented through music in traditional contexts like songs, advertisements, and live performances and typical political contexts like national anthems and party-political broadcasts. Although past study has shown that music can carry political signals, there are differing views on the precise relationship between music and politics (Way, 2019). Much popular music has the propensity to be reflective and parochial in its subject matter (Chornik, 2018).…”
Section: Political Communication: Music and Politicsmentioning
confidence: 99%
“…He created songs and staged performances against apartheid that inspired the downtrodden black population of South Africa to overthrow the Afrikaner ruling class (Onyebadi & Mbunyuza-Memani, 2017). Therefore, understanding the connection between music and politics and the meaning conveyed in music can be improved by studying sociopolitical movements through framing analysis (Way, 2019). Such a study enhances the science of political communication by demonstrating not just what empty box volunteers communicated to the sole candidate for the Humbang Hasundutan (Humbahas) Regional Head Election through a song but also how it was accomplished.…”
Section: Political Communication: Music and Politicsmentioning
confidence: 99%
“…Hunter and Schellenberg, 2010; Juslin and Sloboda, 2013). Cultural and communicative analyses have tended towards semiotic or social semiotic models (Machin and Richardson, 2012; Tagg, 1987; Van Leeuwen, 1999; Way, 2019). Rhetorical approaches tend towards issues of style, symmetry, and epideixis (Graham and Luttrell, 2019).…”
Section: Music As Meaning Versus Music As Symbolic Actionmentioning
confidence: 99%